Digital Diplomacy as us Interests in Central Asia (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Today, digital diplomacy is becoming an important tool in the United States' foreign policy in the Central Asian region. In the context of globalization and the growth of digital technologies, digital diplomacy is used by the United States to achieve political, security, economic, and social goals.